2016
DOI: 10.29048/makufebed.206625
|View full text |Cite
|
Sign up to set email alerts
|

Hava Kirleticilerin Bitkilere Etkileri

Abstract: Dünyada hızlı gelişen kentleşme ve endüstrileşme ile bilinçsiz tarımsal uygulamalar sonucunda ciddi hava kirliliği problemleri ortaya çıkmıştır. Çeşitli endüstriyel kaynaklardan atmosfere verilen hava kirleticiler, başta insanlar olmak üzere bitkiler ve hayvanlar üzerinde önemli zararlara neden olmaktadır. Dolayısıyla bu çalışmada, başlıca hava kirleticilerine yer verilmiş ve bunların bitkiler üzerine etkileri incelenmiştir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Many international studies have been carried out on the determination of bioclimatic comfort zones in Turkey in recent years. To determine the bioclimatic comfort conditions of many different cities in Turkey for certain years; Zeren Cetin and Sevik [5], Kilicoglu et al [54] have used the PET index [3,55,62,70]; Cetin [45] have relied on PET and DI index methods; while Cetin et al [8], Adıguzel et al [60]; Zeren Cetin et al [4] have adopted the method of environmental climatic parameters [35-40, 46, 47, 60, 62, 70, 71]. This study is the first study on the bioclimatic comfort areas of Bartin for determining the effect of land use a land cover change on sustainable forest areas.…”
Section: Discussionmentioning
confidence: 99%
“…Many international studies have been carried out on the determination of bioclimatic comfort zones in Turkey in recent years. To determine the bioclimatic comfort conditions of many different cities in Turkey for certain years; Zeren Cetin and Sevik [5], Kilicoglu et al [54] have used the PET index [3,55,62,70]; Cetin [45] have relied on PET and DI index methods; while Cetin et al [8], Adıguzel et al [60]; Zeren Cetin et al [4] have adopted the method of environmental climatic parameters [35-40, 46, 47, 60, 62, 70, 71]. This study is the first study on the bioclimatic comfort areas of Bartin for determining the effect of land use a land cover change on sustainable forest areas.…”
Section: Discussionmentioning
confidence: 99%
“…Causes leaves to change from horizontal to vertical (epinastia), shedding of leaves and fruits (abscess), and chlorosis (Gheorghe et al, 2011;Yücedağ et al, 2016).…”
Section: Accumulation Of Cement Dusts In Vegetation Can Inhibit Respi...mentioning
confidence: 99%
“…They cause disruptions in photosynthesis and enzyme mechanisms and inhibit chlorophyll synthesis and germination. (Yücedağ et al, 2016).…”
Section: Heavy Metalsmentioning
confidence: 99%
“…However, depending on the use of fossil fuels and industrial activities, pollutants enter the atmosphere and can be included in the precipitation. Thus it can lead to negative physico-chemical contents that affect plant growth (Yücedağ & Kaya, 2016). In some studies, it has been reported that snowmelt water contains some elements in higher proportions than rainwater, and surface water is affected by the melting of snow (Hagen & Langeland, 1973;Johannessen & Henriksen, 1978;Jeffries, 1990;Pehlivan, 2016;Galeczka, Sigurdsson, Eiriksdottir, Oelkers, & Gislason, 2016).…”
Section: Introductionmentioning
confidence: 99%